“How do I look?” a study on the sociocultural acceptance towards appearance among female university students / Josephine Josli, Patricia Pawa Pitil and Floranordiana Ennya Niru - Josli, Josephine; Pitil, Patricia Pawa; Niru, Floranordiana Ennya (Universiti Teknologi MARA, Perlis, 2023)
This study aims to explore the sociocultural acceptance towards the appearance concerning body mass index (BMI) among female university students (N = 414). The female students were selected from various faculties using a stratified sampling technique through an online platform in a cross-sectional study. The Sociocultural Attitudes Towards Appearance Questionnaire – 4 was employed to measure the internalisation of appearance ideals and appearance-related pressure, such as internalised muscular-athletic, internalised thin-low body fat, as well as pressures from family, peers, and media. Sociodemographic and body weight and height were also reported. The factor of internalised thin-low body fat has the highest mean score, while the lowest mean score was pressure from peers. Pressures from family, peers, and media were significantly different among the BMI categories. However, the finding contradicted with internalised muscular-athletic and internalised thin-low body fat. There should be concerns as significant differences were found in the pressures of family, peers, and media, in which obese females perceived the highest in those variables compared to other weight categories. The results suggest that the use of media among females warrants extra control as it has the highest among obese females towards their appearance. Educational actions are strongly advised so that family and friends would be more supportive in body weight management among females instead of pressuring them on their appearance. These findings suggest that other sociodemographic should be investigated to understand their influence in the internalisation of appearance ideals and appearance-related pressure among females.